CALCULATING REACHABLE WORKSPACE ON ROBOT STEWART-PLATFORM - PRASETYO (NIM : 23108010); pembimbing : Dr. Ir. Indrawanto, TEGUH
Stewart-platform robot is a parallel robot that is currently being developed at the Robotics and Automation Laboratory of Mechanical Engineering, ITB. One of the things that continue to be developed is the control system. To get a good control system design, one of the things needs analysis calculation robot position. In the analysis of the position calculation, need to know the reachable workspace of the robot. Calculation method used to determine the area reachable workspace is the inverse Kinematic. By plotting the inverse Kinematic calculations with mechanical limitations of the actuator, then can be found form of space of reachable workspace. If the projection space of work expected of Stewart-platform robot is cylindrical, then for the reachable workspace that has a working projection orientation Roll, Pitch, Yaw ± 10o, ± 20o and ± 30o, obtained its cylinder volume is 2763.2 cm3, 357. 86 cm3 and 4.775 cm3.